2015
DOI: 10.1007/s12602-015-9193-7
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Up the Production of Recombinant Antimicrobial Plantaricin E from a Heterologous Host, Escherichia coli

Abstract: Enhanced production of heterologously expressed plantaricin (plnE) from Escherichia coli BL21 (DE3) was achieved from a small- to large-scale batch culture. Starting from a 15-ml shake-flask culture grown in Luria-Bertani (LB) broth, the protein expression could be scaled up using 50 ml, 100 ml, 1 l, and 2 l batch culture. Using similar condition, plantaricin E (PlnE) was successfully expressed in a 30-l stirred fermenter. The protein was expressed as TRX-(His)6-fusion protein and separated by Ni(2+) affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Therefore, there are no general rules. Pal and Srivastava ( 2015b ) found higher Plantaricin E yield in LB than in TB, while Kuthning et al ( 2015 ) found the best-producing conditions for Bliα and Bliβ lichenicidin peptides was medium M compared to 2 × YT, SB, TB, and LB-Kelly.…”
Section: Culture Conditions For Bacteriocin Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there are no general rules. Pal and Srivastava ( 2015b ) found higher Plantaricin E yield in LB than in TB, while Kuthning et al ( 2015 ) found the best-producing conditions for Bliα and Bliβ lichenicidin peptides was medium M compared to 2 × YT, SB, TB, and LB-Kelly.…”
Section: Culture Conditions For Bacteriocin Expressionmentioning
confidence: 99%
“…In addition, the use of fusion protein partners can increase the expression level, enhance protein solubility and assist in correct folding and disulfide bond formation (Ingham and Moore, 2007 ). Common fusion partners used for bacteriocin production include the cellulose binding domain (CBD cenA ) (Klocke et al, 2005 ), maltose-binding protein (MBP) (Quadri et al, 1997 ; Kim et al, 2006 ), thiorredoxin (Trx) (Gibbs et al, 2004 ; Richard et al, 2004 ; Beaulieu et al, 2007 ; Yildirim et al, 2007 ; Jasniewski et al, 2008 ; Caetano et al, 2011a ; Liu et al, 2011 ; Pal and Srivastava, 2014 , 2015a , b ; Jiang et al, 2016 ; Mustopa et al, 2016 ; Meng et al, 2017 ; Tang et al, 2018 ) and the small ubiquitin-related modifier SUMO (Wang et al, 2013 ).…”
Section: Plasmids For Bacteriocin Expression In E Colimentioning
confidence: 99%
See 1 more Smart Citation
“…In the past five years, there are several published attempts to produce AMPs using fermenters at scales and productivity larger than that of using shake flasks aforementioned. E. coli has been utilized to produce AMPs including plantaricin E (Pal and Srivastava 2015) and Pa-MAP 2 (Sousa et al 2016), as well as P. pastoris for MP1102 (Zhang et al 2015b), NZ17074 (Wang et al 2014), and apidaecin (Cao et al 2018;Chen et al 2017), and B. subtilis for gageomacrolactins (Tareq et al 2013). Unlike growing cells in shake-flasks, critical parameters are controlled in fermenters including temperature, pH, and dissolved oxygen (DO).…”
Section: Scale Up Productionmentioning
confidence: 99%
“…for bulk production of chemicals, metabolites and enzymes [ 23 , 28 ] as well as for in situ delivery of vaccines [ 8 , 11 , 12 , 32 , 50 ]. Anti-microbial features, such as plantaricin production, are also of growing importance [ 33 ].…”
Section: Introductionmentioning
confidence: 99%